ORIGIN OF STRONG INTRAPLATE EARTHQUAKES - Vinnik L.P. (My University, 1989)
The foci of strong tremors are generally confined to long-lived active faults. However, some earthquakes occur at great distances from the boundaries of lithospheric plates, and the seismic events which occur in the stable continental crust (SCC) constitute a special category. The purpose of the present article is to compare and logically connect certain properties of seismogenic zones of SCC regions, and to come up with a hypothesis (susceptible to experimental verification) that could serve as a starting point for the development of geophysical methods for identifying zones of high seismic risk in SCC regions.